Numerical Model of Wave Transmission on Curtain-Wall Pile Breakwater with DualSPHysics - Tahalele, Marcio; Khaldirian, Muhammad Farizqi (Jurnal Teknik Pengairan: Journal of Water Resources Engineering, 2025)
One of the problems often encountered in coastal areas is changes in coastal morphology caused by wave propagation. Curtain Wall-Pile Breakwater (CPB) is a practical alternative to dampen waves heading towards the shore. This study investigates the wave transmission caused by CPB using the Smoothed Particle Hydrodynamics (SPH) method and compares the experimental results with SPH. SPH was employed using open-source Computational Fluid Dynamics (CFD) software based on the DualSPHysics code. The numerical model (SPH) was made to resemble the experiment. The study was based on the effect of wave period (T) and the ratio between the submerged depth of the wave retaining wall and the water depth (h/d) of the CPB. The results show that CPB is effective in reducing incident waves. The effectiveness is seen from the resulting Transmission Coefficient (Kt) value. The baseline model Kt value is 0.854, and the Kt value with CPB is 0.693. The research findings show that the wave period (T) dramatically affects the wave transmission caused by CPB. The resulting Kt value decreases with increasing wave steepness (Hi/L), increasing incident wave height (Hi), and wave period (T). In addition, the increase in h/d also affects the Kt value, i.e., the resulting Kt value gets smaller. This study concludes that CPB can reduce the incident wave, thereby reducing the impact of waves on the protected side. Therefore, in designing a breakwater, it is necessary to consider the wave period (T) and the permeability level of the breakwater (h/d variation).